Affect, emotion, and rhetorical persuasion in mass communication - Zhang, Lei 1974 February 17-; Clark, Carlton (New York Routledge, 2019)
"This volume examines the interplay between affect theory and rhetorical persuasion in mass media communication. It is divided into three sections--affect theory, general case studies, and case studies on the 2016 U.S. Presidential Election--and offers perspectives from authors around the world. With chapter-by-chapter discussion questions, as well as links to further research online, this text offers both a theoretical overview and the latest research in the field. Interdisciplinary in approach, it will be of use to advanced undergraduate and graduate students in communication, rhetoric, political science, social psychology, sociology, and cultural studies"-- Provided by publisher.
Three paradigms of affect: the historical landscape of emotional inquiry / Kevin Marinelli -- Bridging the affect/emotion divide: a critical overview of the affective turn / Paul Stenner -- We have never been rational: a genealogy of the affective turn / David Stubblefield -- Affective rhetoric: what it is and why it matters / Samuel Mateus -- White Nationalism and the rhetoric of nostalgia / Michael Mayne -- They believe their belief: rhetorically engaging culture through affect and ideology / Phil Bratta -- Governing bodies: the affects and rhetorics of North Carolina's House Bill 2 / Julie D. Nelson -- How affect overrides fact: anti-Muslim politicized rhetoric in the post-truth era / Lara Lengel and Adam Smidi -- "Lee's filling tastes Grant!": the affect of Civil War archetypes in beer commercials / Lewis Knight and Chad Chisholm -- Disgusting rhetorics: "what's the warts that could happen?" / Jaimee Bodtke and George F. (Guy) McHendry, Jr. -- Aestheticizing the affective politics of "If you see something, say something" / Charlotte Kent -- Gratifications from watching movies that make us cry: facilitation of grief, parasocial empathy, and the grief-comfort amalgam / Charles F. Aust -- The circulation of rage: memes and Donald Trump's presidential campaign / Jeffrey St. Onge -- Feelings Trump facts: affect and the rhetoric of Donald Trump / Lucy Miller -- Affect, Aesthetics and Attention: The Digital Spread of Fake News across the political spectrum / Kayla Keener -- Meta-sexist discourses and affective polarization in the 2018 US presidential campaign / Jamie Capuzza.
Prof. Belinda Espiritu (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Mass media -- Psychological aspects; Mass media -- Social aspects; Mass media -- Political aspects; Mass media -- Influence